ORIENTAÇÃO PARA CONSTRUÇÃO DE CALÇADAS ACESSÍVEIS NO MUNICÍPIO DE JOAÇABA - Lamb, Kathlin Aline; de Marco, Quésia Nagel; Piovesan, Angela Zamboni; Carelli, Jhulis Marina; Foiato, Maiara (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The concept of an ideal sidewalk is one that guarantees a free, safe and comfortable walk for all citizens, but this is not the reality seen in the city of Joaçaba (SC). The University of the West of Santa Catarina (UNOESC) developed an extension project with four objectives: to evaluate the conditions of six public sidewalks of the city; to carry out technical tests with tactile signaling tiles marketed in the region; and elaborate a booklet of awareness regarding the new pattern of sidewalks defined by the City Hall of Joaçaba. Five criteria regarding the quality of the sidewalks were observed: irregular sidewalk, narrow passage, step on the sidewalk, without sidewalk and accentuated ramp. The results were composed in blueprints and digitized subtitles, then were classified according to the NBR 9050: 2015. The data show that the main problem of the walks is the irregular sidewalks and the smallest of them is the lack of sidewalks. This proves that the sidewalks exists, but are broken and in poor condition. The tests carried out with the tactile floors (disruption and dimensions) show that the resistance of the tile satisfies the requirements of NBR 9457: 2013.